2019
DOI: 10.1016/j.bioorg.2019.103031
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of 3,3′-dihydroxycurcumin (DHC) is associated with membrane perturbation

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…Other authors have also reported a high sensitivity of these pathogens to curcumin, although the above-mentioned species have been examined to varying degrees. A lot of data exists for S. aureus (e.g., [ 20 , 32 , 34 , 35 , 37 , 54 ]), while in the case of S. pyogenes [ 20 , 31 , 33 , 55 ], and A. lwoffii [ 20 ], they are few. The very strong antimicrobial activity of curcumin, probably due to the use of acetone as a solvent, was shown in the studies of Lutomski et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have also reported a high sensitivity of these pathogens to curcumin, although the above-mentioned species have been examined to varying degrees. A lot of data exists for S. aureus (e.g., [ 20 , 32 , 34 , 35 , 37 , 54 ]), while in the case of S. pyogenes [ 20 , 31 , 33 , 55 ], and A. lwoffii [ 20 ], they are few. The very strong antimicrobial activity of curcumin, probably due to the use of acetone as a solvent, was shown in the studies of Lutomski et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the activity of curcumin against S. haemolyticus has not yet been studied, whereas the previous results for E. faecalis were similar to our findings. The MIC of reference strains of this species varied between 156 [ 37 ] and 625 µg/mL [ 39 , 40 ] for E. faecalis ATCC 51299 and E. faecalis ATCC 29212, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, phytochemicals have remained the leading source for potential antimicrobial agents, whether investigated independently or in a combination with another substance [2,25]. Recent studies have demonstrated a wide range of antimicrobial properties of curcumin mediated by different mechanisms, such as alteration of gene expression, inhibition of bacterial DNA replication and disruption of the bacterial cell membrane [26][27][28].Literature data demonstrate the beneficial and preventive role of curcumin against various microorganisms [29][30][31]. Despite various studies evaluating the antimicrobial activity of curcumin, further research is required with different concentrations against different strains of microorganisms.…”
Section: In Vitro Antimicrobial Activitymentioning
confidence: 99%
“…In our continuing search for new antibacterial phenolic compounds, we have synthesized and evaluated hundreds of compounds using antibacterial phenotypic assays against gram-positive and gram-negative species [ 13 , 14 , 15 , 16 ]. The structural design of our library of curcumin analogs has been based on phenolic functionality, because most of bacterial division inhibitors display at least one phenol ring [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%